2021
DOI: 10.3390/toxins13040288
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Effects and Intracellular Localization of Bin Toxin from Lysinibacillus sphaericus in Human Liver Cancer Cell Line

Abstract: Binary toxin (Bin toxin), BinA and BinB, produced by Lysinibacillus sphaericus has been used as a mosquito-control agent due to its high toxicity against the mosquito larvae. The crystal structures of Bin toxin and non-insecticidal but cytotoxic parasporin-2 toxin share some common structural features with those of the aerolysin-like toxin family, thus suggesting a common mechanism of pore formation of these toxins. Here we explored the possible cytotoxicity of Bin proteins (BinA, BinB and BinA + BinB) against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Both BinA and BinB are members of aerolysintype β-PFTs and share some structural features with Mpp46Aa (PS2Aa) [11]. Potential application to cancer therapy has been assessed and it has been demonstrated that a high concentration of trypsin-activated Bin toxin (particularly BinB subunit) inhibited cell proliferation of human cancer cell lines [31,32]. Comparative analysis, particularly associated with receptor binding, may help to explore the determinants of the specificity of Mpp46Ab as well as Bin toxins.…”
Section: Discussionmentioning
confidence: 99%
“…Both BinA and BinB are members of aerolysintype β-PFTs and share some structural features with Mpp46Aa (PS2Aa) [11]. Potential application to cancer therapy has been assessed and it has been demonstrated that a high concentration of trypsin-activated Bin toxin (particularly BinB subunit) inhibited cell proliferation of human cancer cell lines [31,32]. Comparative analysis, particularly associated with receptor binding, may help to explore the determinants of the specificity of Mpp46Ab as well as Bin toxins.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 2 × 10 5 cells were plated on Transwell ® system to perform the LA quantification and permeability assay by 0.04% fluorescein (Merck Life Science, Rome, Italy). A total of 2 ×10 4 cells were plated in 96-well plates for the analysis of cell viability by MTT test (Merck Life Science, Rome, Italy) [ 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…The binary toxin is also being studied for its therapeutic role as a potential anti-cancer agent (Luo et al., 2014) . Reportedly, the binary toxin induces apoptotic events in human cancer lines (Chankamngoen, Janvilisri, Promdonkoy and Boonserm, 2020) and targets the mitochondria (Kanwal, Abeysinghe, Srisaisup and Boonserm, 2021) .…”
Section: Challenges and Future Prospectsmentioning
confidence: 99%